Cimarron Artist Wins Awards (Raton Range Raton, NM, 1989)
This article is about B. D. Casey from Cimarron, New Mexico receiving an award at the Arts Fest in Angel Fire, New Mexico.
Newspaper article + photograph of Casey's "Snow Mountain"
Mater List Item # 7
File location is in the New Mexico File Cabinets
Keywords: Casey, B. D. -- Artist; Gorman, R. C. -- Artist; Whitehurst, Jane -- Artist; Granger, Bill -- Artist; Moreno Valley Arts Council; Painting Exhibits; Art Fairs; Artist; Oil Painting; Art Media; Art Awards; Angel Fire, New Mexico; Cimarron, New Mexico; Moreno Valley